(untitled) (Experimental biology, 2015)
Beginning researches on the direction of creation of new medicinal forms from a perspective domestic source – it is necessary to carry out in our appearance phytochemical monitoring of biologically active agents content a making plant. As shows phytochemical monitoring essential oil raw materials, therefore, the first object for development of technology of wound healing preparation is the essential oil, rich chamazulene